2009
DOI: 10.1002/yea.1656
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide expression profiling of the osmoadaptation response of Debaryomyces hansenii

Abstract: The euryhaline marine yeast Debaromyces hansenii is a model system for the study of processes related to osmoadaptation. In this study, microarray-based gene expression analyses of the entire genome of D. hansenii was used to study its response to osmotic stress. Differential gene expression, compared to control, was examined at three time points (0.5, 3 and 6 h) after exposure of D. hansenii cultures to high salt concentration. Among the 1.72% of genes showing statistically significant differences in expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Only recently, species-specific DNA microarray studies have been presented for e.g. Debaryomyces hansenii [40] and P. pastoris [41]. For H. polymorpha , Oh et al , [42] presented a partial, DNA microarray study, followed by a full DNA microarray analysis describing the transcriptional response of H. polymorpha to exposure to cadmium [43].…”
Section: Resultsmentioning
confidence: 99%
“…Only recently, species-specific DNA microarray studies have been presented for e.g. Debaryomyces hansenii [40] and P. pastoris [41]. For H. polymorpha , Oh et al , [42] presented a partial, DNA microarray study, followed by a full DNA microarray analysis describing the transcriptional response of H. polymorpha to exposure to cadmium [43].…”
Section: Resultsmentioning
confidence: 99%
“…The up-regulation of genes involved in protein synthesis during osmotic stress has been reported for the salt-tolerant yeasts H. werneckii and D. hansenii [30,50]. Furthermore, studies on brewing strains of S. cerevisiae concluded that the faster adaption to higher salt concentration compared to a laboratory strain was achieved by higher expression levels of genes involved in protein synthesis [51].…”
Section: Discussionmentioning
confidence: 97%
“…Debaryomyces hansenii is a highly extremophilic yeast. However, unlike in the case of osmotolerance (Arroyo Gonzalez et al 2009), resistance to concentrations of cobalt that are toxic to other similar organisms does not seem to be a pre-adapted characteristic. This is supported by the fact that there is an initial shock when D. hansenni is exposed to Co (II), as indicated by the observation that many of the genes that are upregulated several fold are involved in DNA synthesis and repair.…”
Section: Cell Division and Growthmentioning
confidence: 88%
“…Debaryomyces hansenii is an extremophilic yeast that has been studied for its osmotic stress tolerance, its lipid accumulation and storage, its ability to synthesize various chemicals and enzymes important for industrial applications, and its capability to survive toxic concentrations of the heavy metal cobalt (Breuer and Harms 2006;Seda-Miró et al 2007;Arroyo Gonzalez et al 2009). It is also a highly heterogeneous yeast strain, with two major varieties described, namely, var.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation